The Viral Picture of Well-Being: Biggest Concerns, Losses, and Unintended Gifts of COVID-19 in the Philippines - Tuason, Ma Teresa (Archīum Ateneo, 2023)
The COVID-19 pandemic revealed more than anticipated about global human functioning and resiliency. This Philippines-based study replicated a recent U.S. COVID analysis on psychological well-being (PWB). Factors examined herein were grouped into categories for analysis: 1) predictors of PWB, 2) areas of greatest stress or worry (biggest concerns), 3) perceived or real losses across SES, and 4) identified “unintended gifts” across PWB. Participants (n = 1345) were volunteers who responded to an online survey from August to September 2021, peak of the Delta variant. Three general groups of predictors (biological, psychological, and socio-economic) contributed to PWB. A regression model containing a total of 11 variables was significant, F(11, 1092) = 116.02, p < .00, explaining 53.9% of the variance. The model indicated PWB was significantly predicted by physical health, age, spirituality, emotional loneliness, social loneliness, sense of agency, and income. The strongest predictors of PWB were a sense of agency, social loneliness, and spirituality. Qualitative data analysis was conducted examining biggest concerns, losses due to COVID, and unintended gifts. Top ranking participant concerns were the health of family and friends, personal wellness, and governmental inefficiency/lack of concern. Losses compared to pre-COVID life were analyzed by SES group, with the most frequent responses being missing face-to-face interactions and the freedom to go/do what they please. Low SES groups were most likely to endorse missing everyday routine and experiencing changes in housing conditions due to the pandemic. Unintended gifts of COVID explored by PWB, high PWB individuals significantly appreciated intentional time with family and friends, deepening their spiritual lives, the ability to work from home, less pollution, and more time for physical exercise. Low PWB individuals reported nothing gained, except more time playing video games and watching TV. Those with higher PWB identified more unintended gifts of COVID and coped more actively.